ACCESS TO HEALTHCARE AND LABOUR MARKET PARTICIPATION IN NIGERIA - Andrew A, Igwemma; Callistus; Adaeze Maryann, Agu (International Journal of Multidisciplinary Reseach, 2025)
This study examines the relationship between access to healthcare and labour market participation in Nigeria. Three specific objectives are formulated: to ascertain the extent to which availability of healthcare affects labour market participation in Nigeria; investigate the relationship between healthcare affordability and labour market participation; and to determine the relationship between healthcare acceptability and labour market participation. The study focuses on selected communities in all the five states that make up South East Nigeria. The sample size is 358. The data were collected through structured questionnaire and analyzed using Pearson correlation coefficient. The results reveal that availability of healthcare personnel and facilities has negative correlation and no significant effect on labour market participation, there is significant positive correlation between healthcare affordability and labour market participation and healthcare acceptability correlates positively and significantly with labour market participation. The study concludes that that labour market participation in rural communities in Nigeria is enhanced through healthcare affordability and healthcare acceptability. However, there is still low availability of healthcare personnel and facilities in the rural communities and this is affecting labour market participation. The study recommends that government should build more primary healthcare centers in rural communities, make health insurance scheme enforcement compulsory for all rural residents in Nigeria because when healthcare is available and acceptable, it increases access to healthcare and boosts labour market participation and productivity.